MiR218 Modulates Wnt Signaling in Mouse Cardiac Stem Cells by Promoting Proliferation and Inhibiting Differentiation through a Positive Feedback Loop - Wang, Yongshun (Sci Rep, 2016)
MiRNA expression was determined in both proliferating and differentiated cardiac stem cells (CSCs) through a comprehensive miRNA microarray analysis. We selected miR218 for functional follow-up studies to examine its significance in CSCs. First, we observed that the expression of miR218 was altered in CSCs during differentiation into cardiomyocytes, and transfection of an miR218 mimic or miR218 inhibitor affected the myocardial differentiation of CSCs. Furthermore, we observed that a negative regulator of Wnt signaling, sFRP2, was a direct target of miR218, and the protein levels of sFRP2 were increased in cells transfected with the synthetic miR218 inhibitor. In contrast, transfection with the miR218 mimic decreased the expression of sFRP2 and potentiated Wnt signaling. The subsequent down-regulation of sFRP2 by shRNA potentiated Wnt signaling, contributing to a gene expression program that is important for CSC proliferation and cardiac differentiation. Specifically, canonical Wnt signaling induced miR218 transcription. Thus, miR218 and Wnt signaling were coupled through a feed-forward positive feedback loop, forming a biological regulatory circuit. Together, these results provide the first evidence that miR218 plays an important role in CSC proliferation and differentiation through the canonical Wnt signaling pathway.